Dynamic Portfolio Choice with Parameter Uncertainty and the Economic Value of Analysts’ Recommendations - Cvitanić, Jakša; Lazrak, Ali; Martellini, Lionel; Zapatero, Fernando (Review of Financial Studies, 2006)
We derive a closed-form solution for the optimal portfolio of a nonmyopic utility maximizer who has incomplete information about the alphas or abnormal returns of risky securities. We show that the hedging component induced by learning about the expected return can be a substantial part of the demand. Using our methodology, we perform an “ex ante” empirical exercise, which shows that the utility gains resulting from optimal allocation are substantial in general, especially for long horizons, and an “ex post” empirical exercise, which shows that analysts’ recommendations are not very useful. (JEL C61, G11, G24)